Eksistensi Kesenian Barongan Kusumojoyo Desa Gebang Kecamatan Bonang Kabupaten Demak (Jurnal Seni Tari, 2020)
Barongan, a kind of mask that has face resembling a lion with beautiful feathers decoration, serves as an entertainment in the community. Barongan or most commonly known as Singo Barong, has its own folklore that tells a story of a huge animal (a lion) played by two men, one holds its head and the other hold the tail. The objectives of this research are to describe the performance’s forms and the existence of Barongan Kusumojoyo from Gebang village, Bonang district, Demak regency. The research employed a qualitative method by only focusing on the performance’s forms and existence. The writer employs herself to collect the data, by doing observation, interviews, and some documentation. The researcher used triangulation technique to validify the data; which includes source triangulation, method triangulation, and theory triangulation. The findings of this research show that the performance’s forms of Barongan Kusumojoyo can be seen from its presentation structure and the elements of show. The elements of show appear in motion, makeup, fashion, property, musical accompaniment, and its stage layout. The existence of Barongan Kusumojoy can be seen from the process of training to staging. Barongan performances are made up of imitating animal movements and are improvised in a lively accompaniment. Keywords: Performance’s forms, Existence, Barongan Kusumojoyo